Evaluation of the Implementation of the Christian Religious Education Curriculum Using the CIPP Model: Alignment with the Indonesian Qualifications Framework and Outcome-Based Education - Mersi Prastika Dau; Haryono; Rima Indah Kasiati (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to evaluate the implementation of the Christian Religious Education Study Program curriculum, based on the Indonesian Qualifications Framework (IQF) and an Outcome-Based Education (OBE) approach, at STAK Terpadu PESAT Salatiga using the CIPP (Context, Input, Process, Product) evaluation model. The study employed a quantitative evaluative approach involving 13 lecturers and 86 students as respondents. Data were collected using a closed-ended Likert-scale questionnaire that had undergone validity and reliability testing and were analyzed using descriptive and inferential statistics through Welch’s t-test. The results showed that all CIPP components were categorized as good. The context and input aspects reflected adequate planning and resource availability. However, the process and product components were identified as suboptimal due to insufficient alignment between semester learning plans, active learning strategies, authentic assessment practices, and graduate learning outcomes, and evidence of competency attainment did not demonstrate strong performance outcomes. Inferential analysis showed that there were no significant differences in perceptions between lecturers and students regarding the process (p = 0.602) and product (p = 0.980), with very small effect sizes. These findings indicate perceptual convergence between lecturers and students while highlighting the need to enhance the quality of Outcome-Based Learning and Teaching (OBLT) and Outcome-Based Assessment and Evaluation (OBAE) practices. The findings imply that curriculum development within the Christian Religious Education Study Program should prioritize authentic assessment, strengthen lecturers’ pedagogical competencies, and systematically integrate cognitive, affective, and spiritual dimensions within a holistic and sustainable Outcome-Based Education (OBE) framework.